1999
DOI: 10.11150/kansenshogakuzasshi1970.73.20
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Shiga Toxin-producing Escherichia coli O157: H7 from Processed Salmon Roe Associated with the Outbreaks in Japan, 1998, and a Molecular Typing of the Isolates by Pulsed-field Gel Electrophoresis

Abstract: Shiga toxin-producing Escherichia coil (STEC) O157 were isolated from processed salmon roe which had been a suspected food item in sporadic infections which occurred in Japan in 1998. A total of 45 samples of the processed salmon roe were pre-enriched in trypticase soy broth (TSB) at 36 degrees C for 6 h and novobiocin-supplemented modified EC broth (mEC-NB) at 42 degrees C for 18 h. After the pre-enrichments, the cultures were examined for possible occurrence of STEC O157, using an immunomagnetic separation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Such organisms should not be present on fresh-caught fish (Cha�opadhyay, 2000). The contamination of food of fish origin with pathogenic E. coli probably occurs during handling of fish and during the production process (Ayulo et al, 1994;Asai et al, 1999). …”
Section: Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…Such organisms should not be present on fresh-caught fish (Cha�opadhyay, 2000). The contamination of food of fish origin with pathogenic E. coli probably occurs during handling of fish and during the production process (Ayulo et al, 1994;Asai et al, 1999). …”
Section: Escherichia Colimentioning
confidence: 99%
“…Infection with verocytotoxin-producing strains of E. coli (VTEC) a�er ingestion of fish was recorded in Belgium (Pierard et al, 1999). An outbreak caused by salted salmon roe contaminated, probably during the production process, with enterohaemorrhagic E. coli (EHEC) O157 occurred in Japan in 1998 (Asai et al, 1999). The roe was stored frozen for 9 months but it appears that O157 could survive freezing and a high concentration of NaCl and retained its pathogenicity for humans (Semanchek and Golden, 1998).…”
Section: Escherichia Colimentioning
confidence: 99%
“…It has been reported that at least 10 cells existing in food could cause human illness [6]. But Asai et al [7] found that only 0.75 to 1.5 viable cells of E. coli O157:H7 in salted salmon roe could cause the infection. In order to explain this phenomenon, Makino et al [8] re-estimated the number of E. coli O157:H7 cells in the implicated salted salmon roe from their membrane integrity, cell elongation and pathogenicity for mice, and found that almost all of E. coli O157:H7 cells had entered a viable but nonculturable (VBNC) state, thus the authors suggested that VBNC cells of E. coli O157:H7 in the food should be the source of the outbreak.…”
Section: Introductionmentioning
confidence: 98%
“…The preservation of foods by high salt concentrations has been viewed historically as an effective means of preventing food-borne infections (11,13). However, an outbreak caused by salted salmon roe which was contaminated with enterohemorrhagic Escherichia coli (EHEC) O157 occurred in four independent places in Japan in 1998, with 62 cases reported (1). Since all the causative foods were manufactured by the same company, the salmon roe was probably contaminated with O157 during the production process.…”
mentioning
confidence: 99%
“…Although the definitive source of O157 could not be identified because the roe was stored frozen for 9 months, it appeared that O157 could survive freezing and a high concentration of NaCl (22) and retain its pathogenicity for humans. In addition, it was proved by the most probable number method that about 0.75 to 1.5 viable cells of O157 could cause infection (1). This number was considered to be very low for infection (23).…”
mentioning
confidence: 99%